2021
DOI: 10.21203/rs.3.rs-482043/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiota Associated with Effectiveness and Responsiveness to Mindfulness-Based Cognitive Therapy in Improving Trait Anxiety

Abstract: ObjectiveThe mindfulness based interventions have been widely demonstrated effective on reducing stress, alleviating mood disorders and improving quality of life; however, the underlying mechanisms remained to be fully understood. Along with the advanced research in microbiota-gut-brain axis, this study aimed to explore the impact of gut microbiota on the effectiveness and responsiveness to mindfulness-based cognitive therapy (MBCT) among high trait anxiety populations.DesignA standard mindfulness-based cognit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In full accordance with our results, DSS-induced colitis decreases the richness and diversity of the gut microbiota [53], both of which were reversed by the JW formula, highlighting its contribution to the remodeling of gut microbiota. An imbalanced gut commensal flora often begins with an increased prevalence of the Proteobacteria and Bacteroides thetaiotaomicron, which have been considered potential diagnostic signatures of dysbiosis, depression, and colitis [54,55], and the JW therapy considerably suppressed their colonization. Consistently, our untargeted metabolomics results showed that the JW therapy enhanced neomycin, kanamycin, and gentamicin biosyntheses, which might be attributable to the suppression of pathogen colonization.…”
Section: Discussionmentioning
confidence: 99%
“…In full accordance with our results, DSS-induced colitis decreases the richness and diversity of the gut microbiota [53], both of which were reversed by the JW formula, highlighting its contribution to the remodeling of gut microbiota. An imbalanced gut commensal flora often begins with an increased prevalence of the Proteobacteria and Bacteroides thetaiotaomicron, which have been considered potential diagnostic signatures of dysbiosis, depression, and colitis [54,55], and the JW therapy considerably suppressed their colonization. Consistently, our untargeted metabolomics results showed that the JW therapy enhanced neomycin, kanamycin, and gentamicin biosyntheses, which might be attributable to the suppression of pathogen colonization.…”
Section: Discussionmentioning
confidence: 99%